110k views
2 votes
Let x equal -3m -2n -4.What happens tot he value of x if the value of m increases by 2 and the value of n decreses by 1?

User Snoone
by
5.1k points

1 Answer

5 votes

Problem

Let x equal -3m -2n -4.What happens tot he value of x if the value of m increases by 2 and the value of n decreses by 1?​

Solution

For this case we know that:

x= -3m-2n-4

Now we know that the value of m increases by 2 and the value of n decrease by 1 and the new value of x would be given by:

x = -3(m+2) -2(n-1)-4

And if we solve we ogt:

x= -3m -6 -2n +2 -4

And solving we got:

x= -3m-2n -10+2

x= -3m -2n -8

User Continuation
by
5.0k points